Instagram sebagai Arena Wacana Empati: Analisis Wacana Kritis terhadap Respons Publik atas Kesaksian Korban Film Bid’ah pada Akun @ctd.insider - Irhazt Angga Denilza; Fohan Muzakir (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The rapid development of social media has fundamentally transformed the landscape of social communication, particularly in addressing sensitive issues such as sexual abuse. This study aims to analyze the discourse of empathy that emerged toward victims of sexual abuse at an Islamic boarding school, which went viral through the Instagram account @ctd.insider. This research applies Norman Fairclough’s Critical Discourse Analysis (CDA) framework, focusing on three dimensions: textual analysis, discursive practice, and socio-cultural practice. Data were collected through documentation techniques involving captions, comments, hashtags, and netizen visual reactions to the content posted on April 23, 2025. The results reveal that the use of emotive diction, narrative sentence structures, metaphorical language, and intertextuality with the film Bid’ah played a significant role in constructing the meaning of empathy in the digital space. The public did not merely consume information passively but actively participated in shaping digital solidarity through comments, content dissemination, and emotional expression. This empathy discourse also highlights resistance against traditional religious and gender-based power structures within the pesantren. On the social practice level, public responses via social media contribute to changing societal perspectives on religious authority, gender equality, and victim protection. This study contributes to the growing body of literature on digital empathy and underscores the importance of social media as an arena for producing new social meanings. The findings reinforce the argument that digital media can function as a tool for resisting structural injustice by promoting solidarity discourses and supporting victims' rights.